2013
DOI: 10.1111/aji.12166
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serpin and Cystatin Antiproteases in Mucosal Innate Immunity and their Defense against HIV

Abstract: Antiproteases play diverse roles in nature, from regulating protease activity to innate defense against microorganisms. Recently, antiproteases have been shown to play important roles in HIV pathogenesis including, inhibiting HIV binding and replication and reducing activation and inflammation of susceptible cells. They have also been implicated as one of the initial host responders, in plasma, to control replication of HIV. More recently, antiproteases expressed at the mucosal surface have been linked to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 74 publications
1
30
0
Order By: Relevance
“…Overexpressed proteins in these individuals included many serpins (31), several of which were also overexpressed in the follicular phase in our study, as determined by both proteomic and genomic analyses, consistent with earlier findings (32). Serpins are reported to possess anti-inflammatory properties (33) and are important players in mucosal defense against HIV (32), especially in the eclipse phase (27). However, it is noteworthy that not all serine protease inhibitors we tested in this study (including SLPI and trappin-2) showed significantly different expression in the two menstrual phases.…”
Section: Discussionsupporting
confidence: 91%
“…Overexpressed proteins in these individuals included many serpins (31), several of which were also overexpressed in the follicular phase in our study, as determined by both proteomic and genomic analyses, consistent with earlier findings (32). Serpins are reported to possess anti-inflammatory properties (33) and are important players in mucosal defense against HIV (32), especially in the eclipse phase (27). However, it is noteworthy that not all serine protease inhibitors we tested in this study (including SLPI and trappin-2) showed significantly different expression in the two menstrual phases.…”
Section: Discussionsupporting
confidence: 91%
“…5). Factors overabundant during the follicular phase were associated with biofunctions that underlie cellular adherence and epithelial barrier integrity, as well as inflammation mediation (39)(40)(41). This may help in maintaining an environment less likely to contribute to HIV infection since various studies have highlighted the role of inflammatory conditions such as STIs and some forms of bacterial vaginosis in increasing susceptibility to HIV infection (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Protease inhibitors were found at higher levels during the follicular phase and are known regulators of inflammation. Higher levels of these antiproteases may help to reduce inflammatory processes, while at the same time perform innate antiviral functions (39), which may in turn help prevent the establishment of an HIV founder population if a woman is infected during this time. In fact, higher levels of antiproteases have been associated with HIV resistance in highly exposed seronegative female sex workers (23,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In general, these protease inhibitors function as anti-inflammatory factors by inhibiting the proteases secreted by immune cells, such as neutrophils, which can trigger the activation of the complement system and secretion of other inflammatory mediators that can lead to tissue damage and severe inflammation. 16 Protease inhibitors are expressed throughout the entire FRT, including in the vagina, cervix, uterus and even the fetal membranes. Cervical and vaginal epithelial cells have been shown to express most of these protease inhibitors.…”
mentioning
confidence: 99%